KORELASI PADA KOMPONEN HASIL TERHADAP HASIL BENIH TANAMAN SAWI (Brassica juncea L.) - Erlina Kertikasari; Novi Nurhalimah; Mutia Rahmah; Dewa Gede Suarjaya (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2023)
Mustard is a horticultural crop, the last few years has decreased production. The success of the effort to obtain mustard that have good quality and quantity of yield greatly supported by ability of plant breeders to obtain superior genotypes in selection stage. This research aims to find out correlation between yield components and yield on mustard. The next goal to find out character of yield components that have direct effect on the yield of mustard and can be used as basis for effective selection. The research was conducted in December 2018-March 2019 at Seed Bank and Nursery Agrotechno Park, BUA Universitas Brawijaya, located in Jatikerto Village, Kromengan District, Malang Regency, East Java Province. This research uses materials of 60 genotypes of mustard plants (Brassica juncea L.). The research method used randomized group design (RBD) expanded (augmented design). The treatments in study were arranged into 5 blocks and there were 60 experimental units each consisting of 7 plants. This research uses analysis of variance, covariance, correlation, and path with OPSTAT applications. The components of seed yield were highly significantly correlated, including the number of pods/plants, number of seeds/pods, number of seeds/plants, and harvest index. The number of seeds/pods, number of seeds/plants and seed index can be used as an effective selection basis to decide seed yields on mustard.